Risk Analysis Of Dairy Cow Milk Production - Maulidya Larasati; Wiludjeng Roessali; Agus Setiadi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Dairy farmers need to know the risk management strategies in dairy cow milk production process to reach the optimal production and preventing decrease. Pangudi Mulyo Animal Husbandry Group is a farmer group that engaged in dairy cows business and makes dairy milk as its main product. This study aimed to identify risks and set priorities for handling and analyzing risk management strategies for dairy cow milk production. This research was conducted in December 2019-January 2020 in Pangudi Mulyo Animal Husbandry Group located in Randusari Hamlet, Nongkosawit Village, Gunungpati District, Semarang. The method used in this study was census method, by taking 33 active members of the Pangudi Mulyo Animal Husbandry Group. Data collection was carried out through observation and interviews according to the questionnaire. The data were analyzed using quantitative analysis with the House of Risk (HOR) Phase 1 and Phase 2 methods. The results shows that there were 17 risk events and 17 risk agents in HOR Phase 1 and there were 8 risk agents that needed handling based on the high value of Aggregate Risk Potential (ARP). There are identified 13 risk management strategies obtained from HOR phase 2 in accordance with the Effectiveness of Difficult (ETD) assessment of risk agents that need to be addressed.